POSSIBILITIES OF PROCESSING THE TRIBODIAGNOSTIC DATA (Perner's Contacts, 2015)
As it is difficult to monitor and evaluate the state of operated oil effectively based on individual determinations of many of its tribodiagnostic parameters (TDP), a possibility of processing the procedure of selected methods of multidimensional statistical analysis - principal component analysis (PCA) on the matrix of tribodiagnostic data of worn-out OA-M6 ADS II engine oil and discriminant analysis (DA) – was tried.